Effect of Current Ratio, Debt To Equity Ratio, Return On Assets To Return Share With Earnings Per Share as A Mediation Variable in Sub Sector Companies Transportation And Logistics - Maulidur Nizam (Jurnal Ad'ministrare, 2022)
Sector transportation is wrong one sub sector from sector infrastructure on the Indonesia Stock Exchange (IDX). Infrastructure is one of the determining factors development economy which same importance with factors production general other like capital and power work . To determine the effect of the Current Ratio (CR) on Stock Returns in Transportation and Logistics Sector Companies Listed on the Stock Exchange Indonesia period 2017-2021 . Quantitative data is data or information obtained in form number. In the form of number this so data quantitative can in process use formula mathematics or could also in analysis with system statistics, In this study the data obtained from secondary data, namely www.idx.co.id reports annual report which published to general . The F statistical test aims to determine whether there is an effect of Among all variable independent entered in model regression by together (simultaneously) on the dependent variable tested at the level of significance must be less than 0.05.